2013
DOI: 10.1111/j.1365-2125.2012.04377.x
|View full text |Cite
|
Sign up to set email alerts
|

An oral TRPV1 antagonist attenuates laser radiant‐heat‐evoked potentials and pain ratings from UVB‐inflamed and normal skin

Abstract: AIMSLaser (radiant-heat) evoked potentials (LEPs) from vertex-EEG peak-to-peak (PtP) amplitude were used to determine acute antinociceptive/antihyperalgesic efficacy of ABT-102, a novel TRPV1 antagonist efficacious in preclinical pain models, compared with active controls and placebo in normal and UVB-inflamed skin. METHODSThis was a randomized, placebo-and active-controlled, double-blind, intra-individual, crossover trial. Twenty-four healthy subjects received six sequences of single doses of ABT-102 (0.5, 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 32 publications
(38 reference statements)
6
23
0
Order By: Relevance
“…In a recent experimental pain study in healthy human volunteers, 6 mg single dose of ABT-102 (Cmax, 15 ng ml -1 , Caverage during experiment, 9 ng ml -1 ) demonstrated superior antinociceptive efficacy to etoricoxib and tramadol [31]. Taken together, the model estimated transient body temperature increase is estimated to be 0.6 to 0.8°C at ABT-102 analgesic exposures in humans.…”
Section: Discussionmentioning
confidence: 85%
“…In a recent experimental pain study in healthy human volunteers, 6 mg single dose of ABT-102 (Cmax, 15 ng ml -1 , Caverage during experiment, 9 ng ml -1 ) demonstrated superior antinociceptive efficacy to etoricoxib and tramadol [31]. Taken together, the model estimated transient body temperature increase is estimated to be 0.6 to 0.8°C at ABT-102 analgesic exposures in humans.…”
Section: Discussionmentioning
confidence: 85%
“…Chizh and colleagues reported that TRPV1 antagonists can modestly reduce both hypersensitivity and flare area resulting from UVB inflammation [87]. Further to these observations, a more recent study confirmed the therapeutic effects of TRPV1 antagonists, demonstrating the antinociceptive and antihyperalgesic effects of a new selective drug to these vanilloid channels [88]. Adding to the role of TRPV receptor family in UVB- hypersensitivity, another study claimed that UVB induces expression of TRPV4 channels at the epidermis, eliciting a proalgesic effect [89].…”
Section: Uvb-induced Hypersensitivity: Pharmacologymentioning
confidence: 93%
“…Assuming the effects of LLLT would be localized to the treated area, an intra‐individual design was used to maximize results from the study patients. This design has successfully been used in previous studies investigating various forms of laser therapy …”
Section: Methodsmentioning
confidence: 99%
“…This design has successfully been used in previous studies investigating various forms of laser therapy. 12,[27][28][29][30]…”
Section: Methodsmentioning
confidence: 99%